Treatment of a multicomponent mining effluent using calcium hydroxide in a fluidized bed crystallizer - Maharaj, Chiara (Crystallisation and Precipitation Research, 2016)
Wastewater which primarily emanates from mining operations and manufacturing industries, has the potential for re-use if treated effectively. These wastewaters, which are typically characterized by high concentrations of dissolved inorganic salts are often disposed in evaporation ponds, which promotes the risk of ground water pollution and land wastage. Moreover, this forfeits the potential benefits of valuable salts recovered. The aim of this project was to investigate the treatment of multicomponent saline wastewater rich in sodium and magnesium sulphates, since these salts are prevalent in most wastewater streams. The intention was to treat the wastewater with a calcium hydroxide (Ca(OH)2) suspension in a laboratory scale seeded fluidised bed crystallizer, thereby precipitating gypsum and magnesium hydroxide. The objectives of this study were to investigate how the chosen reactor configuration, feed stream and reagent characteristics affect the conversion and recovery of gypsum and magnesium hydroxide over a range of wastewater concentrations. Particular focus was on reducing the formation of fines through the use of seeds and to get an insight into the possible precipitation mechanisms. It was important that the resulting precipitate product quality favoured effective separation from the treated water stream for re-use. Preliminary experiments were conducted over a feed concentration ranging from 1.5 g/L - 120 g/L (total sulphate salts) which was contacted with a stoichiometric amount of calcium hydroxide with respect to the sulphates in the stream, that is a Ca:SO4 ratio of 1:1 in the fluidised bed crystallizer. These experiments identified a feasible feed concentration range for operation (8 000 -35 000 mg/L). High inlet concentrations (≥ 50 000 mg/L) were not feasible due to rapid formation of a large mass of precipitates which disrupted fluidisation and caused the reactor contents to be elutriated. These high concentrations resulted in high rates of accumulation which necessitated the need for frequent intermittent product removal.